2019
DOI: 10.3390/su11205665
|View full text |Cite
|
Sign up to set email alerts
|

The Circular Economy Strategy in Hospitality: A Multicase Approach

Abstract: The circular economy (CE) is considered a possible solution to problems, such as the increasing global demand for resources, climate change and worldwide pollution. CE can help to transform the hospitality industry from its current linear model of production to a circular one. However, there is a lack of research on circular tourism, therefore, this paper’s main purpose is to shed light on CE strategies—reduction, reuse, recycle, redesign, replace and rethink—developed in the tourism sector, as well as the tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 17 publications
0
35
0
7
Order By: Relevance
“…Rodríguez et al [40] recently found out through an extensive literature review for the search period between 2009 and January 2020 that there are still only 55 articles and books published on the field of CE and tourism. Hence, many authors argue that state of the art in this field is in its infancy, with a reduced amount of literature available and a lack of shared understanding about CE and tourism [38,39,[41][42][43].…”
Section: Circular Tourismmentioning
confidence: 99%
“…Rodríguez et al [40] recently found out through an extensive literature review for the search period between 2009 and January 2020 that there are still only 55 articles and books published on the field of CE and tourism. Hence, many authors argue that state of the art in this field is in its infancy, with a reduced amount of literature available and a lack of shared understanding about CE and tourism [38,39,[41][42][43].…”
Section: Circular Tourismmentioning
confidence: 99%
“…Girard and Nocca (2017, p. 68) pointed out circular tourism as "a model able to create a virtuous circle producing goals and services without wasting the limited resources of the planet that are raw materials, water and energy". However, the literature on CE in the tourism industry is still in its early infancy (Rodríguez-Antón & Alonso-Almeida, 2019). It is understood that by applying the principles of CE, tourism SMEs can contribute to sustainable tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The characteristics of Chinese tourists in 2019, according to COTRI [43], were urban and upper-middle class, although those who came to Europe were of the highest class; of an intermediate age (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44); carried out 90% of their travel in Asia; mainly engaged in tourism activities involving cultural activities, shopping, and urban activities, and traveled on a different tourist calendar from the European one.…”
Section: Contextual Analysis: Spain's Position In Chinese Outbound Tourismmentioning
confidence: 99%
“…As previous research pointed out [9,44], destination sustainability could be improved by means of flow control to avoid overtourism. Thus, the analysis of media data together with other strategic administrative measures could contribute to ensuring sustainability in a destination with a balance among economic, social, and environmental issues.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%